Aerosol remote sensing - Remer, Lorraine; Tanre, Didier; Lenoble, Jacqueline (Springer Berlin Heidelberg, 2013)
This book gives a much needed explanation of the basic physical principles of radiative transfer and remote sensing, and presents all the instruments and retrieval algorithms in a homogenous manner. The editors provide, for the first time, an easy path from theory to practical algorithms in one easily accessible volume, making the connection between theoretical radiative transfer and individual practical solutions to retrieve aerosol information from remote sensing, and providing the specifics and intercomparison of all current and historical retrieval methods.